1994
DOI: 10.1177/0310057x9402200606
|View full text |Cite
|
Sign up to set email alerts
|

Peritonsillar Infiltration with Bupivacaine for Paediatric Tonsillectomy

Abstract: In a double-blind study forty-two children scheduled for elective adenotonsillectomy were randomized to receive peritonsillar infiltration, following induction of anaesthesia, with either 0.25% plain bupivacaine or 0.9% saline, 0.5 mllkg to a maximum of 10 ml. The children were assessed on awakening, and then ID minutes, I hour, 4 hours and 24 hours later. On each occasion the observer gave the child a pain score from 1 (no pain) to 5 (severe pain). The scores on awakening and after 10 minutes were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 11 publications
0
37
1
2
Order By: Relevance
“…On the contrary, some studies concluded that bupivacaine infiltration has no or little effect on postoperative pain. While Broadman et al were unable to show any differences between infiltrations of epinephrine containing bupivacaine and normal saline solutions in terms of postoperative pain scores, Stuart et al found a significant reduction only at postoperative tenth minutes in their clinical trial with the same solutions [25,26]. Egeli and Akkaya did not find any statistically significant difference in postoperative complications and pain control between dexamethasone infiltrated group and the group of placebo with saline at the peritonsillar region [27].…”
Section: Discussionmentioning
confidence: 95%
“…On the contrary, some studies concluded that bupivacaine infiltration has no or little effect on postoperative pain. While Broadman et al were unable to show any differences between infiltrations of epinephrine containing bupivacaine and normal saline solutions in terms of postoperative pain scores, Stuart et al found a significant reduction only at postoperative tenth minutes in their clinical trial with the same solutions [25,26]. Egeli and Akkaya did not find any statistically significant difference in postoperative complications and pain control between dexamethasone infiltrated group and the group of placebo with saline at the peritonsillar region [27].…”
Section: Discussionmentioning
confidence: 95%
“…Bupivacaine infiltration for post-tonsillectomy pain has been extensively studied [1][2][3][4][5][6][7][8][9][10], but its effect remains to be controversial. The previous studies evaluating post-operative pain, use one of the two main study designs: descriptive pain scale (DPS), and visual analog scale (VAS).…”
Section: Introductionmentioning
confidence: 99%
“…The DPS method was developed by Broadman et al [1]. In this study design a blinded observer decides who has more pain, comparing the patients after tonsillectomy [1][2][3][4]. Broadman et al [1], Stuart et al [2] and Kountakis [3] reported no difference between the study and control groups where Hung et al [4] reported better oral intake and less pain in the bupivacaine group.…”
Section: Introductionmentioning
confidence: 99%
“…However, some trials concluded that bupivacaine infiltration has no or little effect on postoperative pain. Stuart et al [27] found significant reduction only at postoperative 10th minutes in their clinical trial with infiltration of epinephrine containing bupivacaine. Recently, a meta analysis by Sun et al [28], concluded that peri-operative bupivacaine infiltration is a safe and effective method for relief of pediatric post-adenotonsillectomy pain.…”
Section: Discussionmentioning
confidence: 94%